Poetic perspective of alterity: dialogues between Rimbaud and Bakhtin - Leão, Maria Eloisa do Amaral (2021)
This paper aims to point out possible connections between cultural psychology and poetry from the utterance “I is another”, extracted from Arthur Rimbaud’s “Letters of the Seer” (1871) and taken as a visionary-poetic perspective for the strand of semiotic-cultural constructivism in psychology. This utterance is addressed to Mikhail Bakhtin’s notions of dialogism and polyphony, in order to express the plurality of otherness experiences in the field of I-other-world relations. Bakhtin (1895-1975) is one of the chief authors for that metatheoretical, methodological and ethical strand in psychology, which focuses on relational processes involved in the I-other relations, taking each co-participant in the relation as an active singularity, constructing senses and meanings of experience. Rimbaud (1854-1891) was a visionary poet, and his poetic perspective of alterity is a fertile ground for a dialogue with the cultural psychology. His “Letters of the Seer” will give support to a reflection on the notions of otherness and dialogicity in the Self.